The Pediocin AcH Precursor Is Biologically Active - Ray, Bibek (American Society for Microbiology, 1999)
The properties of the pediocin AcH precursor, prepediocin AcH, have been studied to gain insight into how producer cells may protect themselves from the activity of intracellular prebacteriocins. The native 62-amino-acid precursor and the 44-amino-acid mature species were expressed in Escherichia coli host strains that lack the leader peptide processing enzyme, PapD. Both forms inhibited the growth of the test bacterium Listeria innocua Lin11, indicating that the native precursor is biologically active. The two species also were synthesized in the context of maltose-binding protein chimeric proteins to facilitate the measurement of their relative specific activities. The chimeric form of the precursor was ∼80% as active as the chimeric mature species. Of relevance to cell protection and pediocin AcH production, it was determined that the precursor is strongly susceptible to inactivation by reducing agents and to degradation by chymotrypsin and endogenous E. coli proteases. Taken together, the results indicate that the activity of prepediocin AcH may have to be controlled prior to secretion to prevent toxicity to the host. Perhaps producer cells avoid membrane damage by maintaining the precursor in a reduced inactive state or by degrading molecules whose secretion is delayed.